2020
DOI: 10.1155/2020/7279509
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Dental Implant Rejection

Abstract: Nowadays, dental implants are a prominent therapeutic approach among dentists for replacing missing teeth. Failure in dental implants is a severe challenge recently. The factors which lead to dental implant failure are known. These factors can be categorized into different groups. In this article, we discussed the immunological aspects of implant failure as one of these groups. Cytokines and immune cells have extensive and various functions in peri-implantitis. The equilibrium between pro and anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 86 publications
1
22
0
1
Order By: Relevance
“…For the BP terms, the DEGs were enriched in the immune response and inflammatory response, and this result was consistent with that of previous studies [ 37 ]. For the CC terms of GO, the DEGs were enriched in the integral component of the membrane, which included 68 DEGs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the BP terms, the DEGs were enriched in the immune response and inflammatory response, and this result was consistent with that of previous studies [ 37 ]. For the CC terms of GO, the DEGs were enriched in the integral component of the membrane, which included 68 DEGs.…”
Section: Discussionsupporting
confidence: 92%
“…The CXCL8, IL-6, and IL-1 β genes are directly involved in the cytokine-cytokine receptor interaction pathway (hsa04060). The hub gene IL-6 is a cytokine that stimulates immune response and is upregulated in peri-implantitis [ 37 ]. SPP1 is also known as OPN, and it is a type of osteoimmunoinflammatory marker related to the inflammation and regulation of cytokine production [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because macrophages are the primary phagocytes activated in the early inflammation stage when the body is exposed to implants [ 23 ], we used here THP-1 monocytes to investigate a potential toxicity of alloys or particles released from the degradation of dental implants, that could promote an activation of immune system. We compared the viability of THP-1 monocytes on polystryrene (CTRL) and S_TiNb surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Hotchkiss et al [ 36 , 37 ] have shown that macrophages are particularly important to this response, ultimately driving the conclusion of the inflammatory phase and recruiting mesenchymal stem cells (MSCs) to begin the reparative phase or recruiting other inflammatory cells to delay the healing response [ 38 , 39 ]. In fact, the polarized subtypes of macrophages have no certain advantages and disadvantages to tissue repair; for example, the formation of the vascular network can promote bone tissue regeneration, while the initiation of angiogenesis depends on M1 macrophages, while M2 macrophages play a role in promoting angiogenesis [ 40 42 ]. In addition, a too long polarization period of M1 macrophages will lead to an increase in the number of M2 macrophages, resulting in increased secretion of fibronectin, resulting in fiber wrapping on the surface of the implant and affecting the attachment of osteocytes to the surface of the implant [ 43 45 ].…”
Section: Classical Dichotomy Model Of Macrophagesmentioning
confidence: 99%